Role of CD38, a Cyclic ADP-Ribosylcyclase, in Morphine Antinociception and Tolerance - Hull, Lynn C. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Our previous studies have demonstrated that an increase in intracellular levels of Ca(2+) in neurons is an important component of both the antinociception produced by morphine and morphine's tolerance. The present study tested the hypothesis that the Ca(2+) signaling second messenger, cyclic ADP-ribose (cADPR), derived from CD38 activation participates in morphine antinociception and tolerance. We first showed that morphine's antinociceptive potency was increased by the intracerebroventricular injection of CD38 substrate β-NAD(+) in mice. Furthermore, morphine tolerance was reversed by intracerebroventricular administration of each of three different inhibitors of the CD38–cADPR–ryanodine receptor Ca(2+) signaling pathway. These inhibitors were the ADP–ribosylcyclase inhibitor nicotinamide, cADPR analog 8-bromo-cADPR, and a large dose of ryanodine (>50 μM) that blocks the ryanodine receptor. In CD38 gene knockout [CD38(−/−)] mice, the antinociceptive action of morphine was found to be less potent compared with wild-type (WT) mice, as measured by tail-flick response, hypothermia assay, and observations of straub tail. However, there was no difference in locomotor activation between CD38(−/−) and WT animals. It was also found that less tolerance to morphine developed in CD38(−/−) mice compared with WT animals. These results indicate that cADRP–ryanodine receptor Ca(2+) signaling associated with CD38 plays an important role in morphine tolerance.